Does Risk Change Simply Indicate Current Risk for Recidivism or Something More? A Review of the Predictive Value of Intraindividual Change - Davies, Simon T. (Criminal justice and behavior, 2023)
In this review article, we critically analyze the relationship between change in dynamic risk (i.e., intraindividual change) and recidivism. We start by reviewing the empirical evidence, which indicates intraindividual change is associated with recidivism. However, we highlight how the predictive value of change scores needs careful interpretation. The finding that change scores predict incrementally over baseline scores may simply reflect the improved accuracy of a more recent assessment. Alternatively, the degree of change preceding the reassessment may be relevant in addition to the current level of dynamic risk at reassessment. We propose theoretical reasons why past change may be relevant for prediction beyond current risk scores. Furthermore, the empirical evidence suggests prior change may contain information not solely reflected within the current risk score, but the current evidence has several limitations. Due to the important implications for correctional practice, we encourage further research that more directly examines this question.